Health professionals involved in cancer care coordination: Nature of the role and scope of practice. Issue 4 (August 2018) - Haynes, Kerry; Ugalde, Anna; Whiffen, Rachel; Rogers, Megan; Duffy, Mary; Packer, Chris; Spence, Danielle; Dowling, Anthony; Poon, Peter; Livingston, Patricia
Abstract: Background: Cancer treatment can be complex; and coordination of cancer care across different treatments and health settings is essential to high quality health care. Objective: The aim of this study was to determine the location and scope of practice of health professionals involved in cancer care coordination in Victoria, Australia. Methods: The study design was cross-sectional. An online survey was disseminated through 14 peak organisations for oncology health professionals to individuals whose work involved coordinating the care of cancer patients. Findings: Analysis was conducted on a sample of 91 survey respondents. Only 26.4% (n = 24) reported a job title of Cancer Care Coordinator. Overall, 67.0% (n = 61) reported they were specifically funded to coordinate the care of cancer patients and 30.8% (n = 28) devoted all their time to this role. The majority worked in public health services (n = 73, 80.2%) and 37.4% (n = 34) were located in rural areas. Compared with their metropolitan counterparts, rural coordinators were more likely to be funded by philanthropy (p = 0.002); work part-time (p = 0.017); and work with patients in the community (p < 0.001). In 37.4% (n = 34) of cases patients were required to have a particular type of cancer to receive care coordination. Positions funded by philanthropy were more likely to have this requirement (p = 0.002). Conclusion: Health professionals undertaking cancer care coordination are diverse and the service offered differs according to location and funding source. There may be inequities in care, with people living in particular areas, attending particular health services or with certain tumour types more likely to receive cancer care coordination.